A Study of the Production of Iron Age Clay Figurines from Jerusalem. (October 2014) - B -S, D; D, E D.
Abstract : The paper presents the results of a recent petrographic study that analyzed over 100 Iron II clay figurines found in and around the City of David, Jerusalem. The study was essentially the first archaeometrical analysis of the production mode of domestic cultic objects in the southern Levant. The paper also discusses the differences in production modes between household and temple cultic assemblages and assesses their importance in interpreting Iron Age cultic practices. These differences may help to discount several current theories regarding religious rituals and the production and distribution of cultic objects during the Iron Age.